New Approximation Schemes for Two Asymptotically Perturbed Nonexpansive Nonself Mappings: Nattanawan Piwma, Tanakit Thianwan - Team, Support (Thai Journal of Mathematics, 2016)
In this paper, we introduce and study a new type of two-step iterative scheme for two asymptotically perturbed nonexpansive nonself-mappings in a uniformly convex Banach space. Weak and strong convergence theorems are established for the new two-step iterative scheme in a uniformly convex Banach space. The results obtained in this paper generalize and reﬁne some known results is the current literature.